Debt consumption: The Islamic framework perspective - Rahim, Hainnuraqma; Abdul Khir, Mohamed Fairooz; Awang Tuah, Siti Normah; Bakar, Mohd Hafiz; Hj Mohd Zain, Zainab (Journal of Islamic, Social, Economics and Development, 2025)
Various theories, models and approaches have been introduced by Western scholars in explaining and delving into consumers’ behaviour including the consumers’ theory related to their behaviour in debt practice. Based on the model and approach constructed by the Western scholars, the idea raised has placed the maximum satisfaction of individuals in the theory of consumption as the main aim, although they adopt the method of debt. Nonetheless, according to the Islamic perspective, this theory and understanding do not stay in line with the concept of debt in the activity of consumption. This article aims to build the conceptual framework of the consumption of debt based on the Islamic perspective. The methodology applied to produce this article is the document study, concerning the evidence of the Quran, hadiths, and the views of the fuqaha through past studies on debtors’ behaviour. This article is divided into two sections. Firstly, the discussion on the inaccuracy of the theory of conventional economic consumption about consumers’ behaviour in their debt practice. Secondly, the consumption of the conceptual framework of the debt concept is based on an Islamic perspective. The findings of this study will lead to the construction of the conceptual framework on the consumption of debt based on Shara’.